Taxonomic revision of Molineria species in peninsular Malaysia and their agronomic requirements - Shahari, Rozilawati (2014)
The genus Molineria is mainly distributed in the tropical region of Africa and South East Asia. There are five species of Molineria recorded in Malaysia but only two species were recorded in Peninsular Malaysia which are M. latifolia and M. capitulata. The fruit of Molineria species is of high interest because curculin found in the fruit is a type of sweet proteins and a taste modifying proteins, which change a sour taste into a sweet taste. Morphological variations were detected among these plants between population and localities. The importance of curculin found in the fruit has been discussed but cultivation of Lemba for fruit production has not been established and to date, all plants are considered as wild and underutilized. Therefore, comprehensive studies were set up to identify varietal differences among Lemba and to establish the cultivation of Lemba for its fruit production. The objective of this study were : (1) to identify, describe and classify Molineria species and variety from Peninsular Malaysia, (2) to determine suitable planting medium and shade requirement for growth of two Molineria species under nursery conditions, and (3) to determine the effect nitrogen and potassium rates on growth and yield of two Molineria species under field conditions. The first study was on the morphological and taxonomic characterization for identification of new Molineria species in Peninsular Malaysia. Materials for this study were obtained from both field and herbarium collection. The type specimen of M. latifolia var. megacarpa deposited at Royal Botanic Garden Kew (RBGK) and the other recorded and previously described M. latifolia var. latifolia were referred to and used for cross reference. Based on the morphological and taxonomic characterization, seven species of Molineria namely M. latifolia, M. capitulata M.rubriclavata, M. atropurpurea, M. nitida, M. trichobunda, and M. erythrofolia were recorded found in Peninsular Malaysia. The second study was on the growth performance of M. latifolia var. megacarpa and M. rubriclavata under nursery condition as affected by light intensity and planting media. The plant were grown under 2 shade levels consisting of 50% and 70% shade. Top soil, peat growth and sand were used as growing medium at 10 different ratios. Growth parameters such us plant height, nunber of leaves and fresh and dry weight were collected. Based on this study, the best shade level for both varieties was 70%. This study concluded that the best media for maintaining Molineria species under nursery condition is 1:3:1 and 2:3:1 (top soil:peatgro:sand) media composition for M. latifolia var. megacarpa and M. rubriclavata, respectively. The third study was on the vegetative components and yield of M. latifolia var. megacarpa and M. rubriclavata under field condition as affected by nitrogen and potassium. Single fertilizer (Urea, and Muriate of Potash) was used as N and K sources. Sixteen treatment combinations of nitrogen and potassium were used. Data such as plant height, number of leaf, number of inflorescence, yield and nutrient concentration in plant tissue were taken. Therefore the recommended fertilizer rate for M. latifolia var. megacarpa is 80:40:120 (N:P205:K20) kg/ha and for M. rubriclavata was 120:40:120 (N:P205: K20) kg/ha. M rubriclavata is recommended as new crop for cultivation because it produces higher yield compared to M. latifolia var. latifolia.